2022
DOI: 10.5009/gnl210567
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Status on Mortality in Patients with Hepatocellular Carcinoma: A Korean National Cohort Study

Abstract: Background/Aims We studied the impact of socioeconomic status (SES) on mortality in hepatocellular carcinoma patients and analyzed the effect of SES on initial treatment allocation. Methods A cohort study was conducted using data from the National Health Insurance Service-National Sample Cohort of Korea. A total of 3,032 hepatocellular carcinoma patients who were newly diagnosed between January 2003 and December 2013 were included. Income level was categorized as Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Patients with higher financial hardship ratings had worse functional wellbeing, lower emotional wellbeing, higher anxiety, and higher depression scores, according to Jacob and colleagues [3]. Socioeconomic status was shown by few studies as an independent risk factor for death in cancer patients [22]. According to research by Hapurachi et al [22], patients with low SES reported lower physical, emotional, spiritual, and social EOL outcomes than those with high SES [5].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with higher financial hardship ratings had worse functional wellbeing, lower emotional wellbeing, higher anxiety, and higher depression scores, according to Jacob and colleagues [3]. Socioeconomic status was shown by few studies as an independent risk factor for death in cancer patients [22]. According to research by Hapurachi et al [22], patients with low SES reported lower physical, emotional, spiritual, and social EOL outcomes than those with high SES [5].…”
Section: Discussionmentioning
confidence: 97%
“…Socioeconomic status was shown by few studies as an independent risk factor for death in cancer patients [22]. According to research by Hapurachi et al [22], patients with low SES reported lower physical, emotional, spiritual, and social EOL outcomes than those with high SES [5]. Following a diagnosis of advanced cancer, poor households in low-income countries are exposed to catastrophic health-related expenses, according to a prospective cohort research by Bates and colleagues [1].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Despite advancements in diagnosis and management, HCC presents significant challenges due to late diagnosis and limited effective treatment options in advanced stages. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“… 1 A significant medical and economic burden have been imposed by this fatal malignancy. 2 Although HCC with early stage can be managed by curative therapies such as resection, liver transplantation, and local ablation including radiofrequency ablation, patients with advanced stage have dismal prognosis. 3 , 4 Currently, the new standard of care for the first-line systemic therapy for unresectable HCC is the combination of atezolizumab and bevacizumab.…”
Section: Introductionmentioning
confidence: 99%